CARBONATE CONTENT IN LIGHT SIEROZEMS (Scientific journal of the Fergana State University, 2025)
The article studies the amount of carbonates (CO3) in irrigated light sierozems. Carbonate soils are analyzed mainly depending on such compounds as calcium carbonate (CaCO3) and magnesium carbonate (MgCO3). Soil carbonation is of great importance when studying their physical properties and determining the chemical and mechanical composition. Irrigated light sierozems are classified as carbonate soils, and it was found that the amount of carbonates (7.24%) in the 103-118 cm layer of soil was higher than in other horizons.